2018
DOI: 10.1101/420653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-glucose Induces Retinal Pigment Epithelium Mitochondrial Pathways of Apoptosis and Inhibits Mitophagy by Regulating ROS/PINK1/Parkin Signal Pathway

Abstract: Diabetic retinopathy (DR) caused visual performance degradation seriously endangers human beings’ health, uncovering the underlying mechanism might shed light on the discovery of DR therapeutic treatments. In this study, we found that the effects of glucose on retinal pigment epithelium (RPE) varies in a dose dependent manner, high-glucose promotes ROS generation and cell apoptosis, inhibits mitophagy as well as proliferative abilities, while low-glucose induces ROS production and cell mitophagy, but has littl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In HG-induced retinal pigment epithelium in a dosedependent manner, HG promoted reactive oxygen species (ROS) production and apoptosis and inhibited autophagy and proliferation, while low glucose induced ROS production and autophagy but had little effect on apoptosis and proliferation (43). Consistent with the literature, this research found that participants who reported using HG-induced retinal pigment epithelium played an important role in the development of DR.…”
Section: Discussionsupporting
confidence: 83%
“…In HG-induced retinal pigment epithelium in a dosedependent manner, HG promoted reactive oxygen species (ROS) production and apoptosis and inhibited autophagy and proliferation, while low glucose induced ROS production and autophagy but had little effect on apoptosis and proliferation (43). Consistent with the literature, this research found that participants who reported using HG-induced retinal pigment epithelium played an important role in the development of DR.…”
Section: Discussionsupporting
confidence: 83%
“…CSE-induced insufficient mitophagy and abundant damaged mitochondria are frequently caused by oxidative stress [23]. After CSE exposure, ROS increased, whereas the activities of T-SOD and GSH-PX were downregulated in BEAS-2B cells.…”
Section: Ecc-byf III Improved Cse-induced Oxidative Stress In Beas-2b...mentioning
confidence: 99%
“…As there is little research on effects of high glucose concentration on fish cells in vitro, the present study referred the literatures from other species (19)(20)(21)(22)(23)(24)(25) . The treatment of high glucose on cells usually used the medium containing 20 mM, 25 mM, 33 mM or 50 mM of glucose.…”
Section: Glucose Concentration In Medium Of High Glucose Conditionmentioning
confidence: 99%